"Digital design" and three flows of ideas. Issue 5 (3rd September 2022) - Kim, Jeonghyun; Jeon, BongHee
ABSTRACT: The term "digital design" has become complex and multifaceted. This testifies that this dynamic term has been used in various ways across theory and practice in the field of architecture. Throughout its history, various meanings and interpretations have been layered and overturned sometimes. Through this study, by tracing the historical development of "digital design", we could understand the fundamental "ideas" that is underneath seemingly various and unrelated series of contemporary design experiments. For this reason, this paper suggests three flows of ideas, "Mathematics and Function", "Nature and Structure", "Imagination and Form", that integrate various architects and their works. Graphical abstract: uf0001